Pengaruh Keputusan Pendanaan, Investasi, dan Dividen Terhadap Nilai Perusahaan - Laily Zulfa Rachmawati; Chasan Azari; Setya Prihatiningtyas (Journal Of Accounting and Business, 2022)
Tight competition in the business world causes every company to compete intensely, especially for market opportunities. Efforts that can be made by the company are through increasing the value of the company so the company’s goals are achieved. A company value’s can increase through several relevant financial decisions such as funding, investment, and dividend decisions. Funding decisions in the study were measured by the debt to Equity Ratio (DER), investment decisions were measured by Capital Expenditure to Book Value of Assets (CPA/BVA), and dividend decisions were measured by Dividend Payout Ratio (DPR). The purpose of this study is to determine the effect of funding, investment, and dividend decisions on the value of companies on infrastructure, utilities, and transportation sector companies listed on the IDX for the period 2017-2019. Samples in this study are 10 companies are obtained. The data analysis technique used is multiple linear regression. This study result showed that DER, CPA/BVA, and DPR simultaneously or together affect a firm’s value.